PENGARUH LAYOUT DAN STANDARD OPERATING PROCEDURE TERHADAP PRODUKTIVITAS KARYAWAN EMP MALACCA STRAIT PSC - Eka Noviati; Imam Wibowo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This research aims to know layout and standard operating procedure impact to company’s productivity. Population from this research are employee production division of EMP Malacca Strait PSC as more as 200 persons and sample used are 115 respondents. Research method used is quantitative method, analysis technique multiple regression and simple regression. Research result showing that layout and standard operating procedure partially and together had a positive and significant to productivity. Particularly in production, it is still necessary to make improvements in terms of the tidiness of the layout area, which is further enhanced by providing training and continuous understanding of standard operating procedures and scheduled 5R activities every day.